Epigenetic Regulation Mediated by Methylation in the Pathogenesis and Precision Medicine of Rheumatoid Arthritis - Guo, Shicheng; Xu, Lingxia; Chang, Cen; Zhang, Runrun; Jin, Yehua; He, Dongyi (Frontiers in Genetics, 2020)
Rheumatoid arthritis (RA) as a complex disease is thought triggered by interaction between genetics and environment, especially the shared epitope (SE) and cell surface calreticulin (CSC) theory. However, all the evidence shows genetic diversity and environment exposure cannot explain all the clinical characteristics heterogeneity of rheumatoid arthritis. In contrast, recent studies demonstrate that epigenetics play important roles in the pathogenesis of rheumatoid arthritis, especially DNA methylation and histone modification. DNA methylation and histone methylation are involved in innate and adoptive immune cell differentiation and the migration, proliferation, apoptosis, and mesenchymal characteristics of fibroblast-like synoviocytes (FLS). Epigenetic mediated regulation to immune genes and inflammation pathway provides well explanation to dynamic expression network of rheumatoid arthritis. In this review, we summarized the comprehensive evidence to show methylation modification occurred in DNA and histone are significantly involved in the pathogenesis of rheumatoid arthritis and could be applied as the promising biomarker in the disease activity and drug response prediction. We also explained the opportunity and challenge of the current epigenetics research in rheumatoid arthritis. In summary, epigenetic modules provide possible interface through which genetic and environmental risk factors connect together to contribute to the susceptibility and pathogenesis of RA. Meanwhile epigenetic regulators provided promising drug targets to develop novel therapeutic drugs for rheumatoid arthritis. Finally, DNA methylation and histone modification will be important features to provide better rheumatoid arthritis subtype identification to accelerate personalized treatment and precision medicine.